Indigenous perceptions of climate anomalies in Malaysian Borneo - Narayanan, A/L N. Kulathu Ramaiyer; Gevelt, T. van; Abok, H.; Bennett, Mia; Fam, S.D.; George, F.; Low, C. T.; Zaman, Tariq (Elsevier Ltd., 2019)
Local perceptions of climate anomalies influence adaptation behaviour. Specifically, perceptions that are more accurate and homogenous at the community-level are more likely to facilitate the collective action required to adapt to the local effects of climate anomalies experienced by many indigenous communities. We combine primary data on perceptions of climate anomalies from 200 individuals in six Penan villages in Sarawak, Malaysia with instrumental climate data. We find that perceptions of climate anomalies vary substantially in terms of occurrence and magnitude, and do not generally correlate with instrumental climate data. We operationalise the Penan forest sign language (Oroo’) as a measure of traditional ecological knowledge (TEK) and find only weak evidence of a systematic statistical association with perceptions of climate anomalies among our sampled respondents. Our findings suggest caution in advancing adaptation strategies in indigenous communities that are predominantly premised on TEK. Instead, our findings suggest that in designing adaptation measures, indigenous communities may benefit by engaging in forums where community members and external stakeholders can come together, share their perceptions and observations of climate change, and reach a collective consensus on the community-level effects of climate change and pathways towards adaptation.